Pre and postnatal exposure to Chikungunya virus does not affect child neurodevelopmental outcomes at two years of age. - Randall Waechter; Erinique Ingraham; Roberta Evans; Nikita Cudjoe; Amy Krystosik; Rashida Isaac; Ashlee Watts; Trevor Noël; Barbara Landon; Michelle Fernandes; Veronica Mapp-Alexander; Priyanka Suresh; et al. (Public Library of Science (PLoS), 2020)
Background The 2005-06 chikungunya virus (CHIKV) outbreak in La Réunion suggested that mothers could transmit CHIKV to their neonates while viremic during the intrapartum period, and more than half of the infected neonates showed impaired neurodevelopment at two years of age. However, data sparsity precluded an overview of the developmental impact of vertical infection within the whole prenatal period. Objective & methods The current study assessed two-year old children born to mothers who were infected during the 2014 CHIKV outbreak in Grenada to determine the neurodevelopmental impact of perinatal CHIKV infection throughout gestation. Mother and child infection status were confirmed by serologic testing (IgG and IgM) for CHIKV. Cognitive, fine motor, gross motor, language and behavioral outcomes were assessed at two years of age on the INTERGROWTH-21st Neurodevelopment Assessment (INTER-NDA). Results No differences in neurodevelopmental outcomes were observed between two-year-old children born to mothers infected with CHIKV during gestation (n = 149) and those born to mothers not infected with CHIKV (n = 161). No differences were found in INTER-NDA scores between children infected with CHIKV (n = 47) and children not infected with CHIKV (n = 592). Likewise, there were no differences between children infected with CHIKV post-partum (n = 19) versus children not infected with CHIKV (n = 592). Conclusion Our findings suggest that children exposed and/or infected with CHIKV outside of the intrapartum period experience no significant neurodevelopmental delay at two years of age, as measured by the INTER-NDA, compared to their unexposed and/or uninfected peers. These results complement those of previous studies which showed a neurodevelopmental risk only for children infected during the intrapartum period, while the mother was highly viremic. These results might be reassuring for women of childbearing age and public health officials in CHIKV-endemic regions.